If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m * 10 + -1m * 2 = 49 Reorder the terms for easier multiplication: 10m + -1m * 2 = 49 Reorder the terms for easier multiplication: 10m + -1 * 2m = 49 Multiply -1 * 2 10m + -2m = 49 Combine like terms: 10m + -2m = 8m 8m = 49 Solving 8m = 49 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Divide each side by '8'. m = 6.125 Simplifying m = 6.125
| 4x-6+1=-19 | | (2x+5)=(6x-15) | | 14-9x=6(-4-3) | | x^2+32=33x | | 84=2(23)+2(w) | | 3a(4+1a)= | | 20+8g=180 | | 4x-6+1=19 | | -4m+7+2m=1 | | 5w^3-4w^2-8w=0 | | 9*x-5=2*x-10 | | 20+808h=1 | | sx+rx=r | | 7x-3(2x-5)=9x | | 1=0.5(9x+4) | | 18x^2-12x=.0 | | 8c-24=8(c+3) | | 3x+3=31 | | 20k=100 | | -3+8(-6k+6)=-11+8k | | 1k+1-8k-36= | | 9x+8=4x-10 | | 6+-5t=14 | | 2n-6=4n-1 | | w-10=-64 | | -2m-7(4+3m)=28+5m | | 7a+26=20a | | 7*(2+n)=(7*2)+(7*1) | | x/5-8=3/10 | | 6t-7=29 | | 7(1+8x)-7x=7+4x | | 8n-4n+8n= |